Implikasi Hukum Lingkungan terhadap Pengelolaan Limbah Plastik dengan Recycle Waste : Studi kasus Gunung Sampah TPST Bantargebang - Diny Widya Evriyanti Simarangkir; Cindy Valentina Natasya Sianturi; Febriyana Nur Aziza Sagita Sari (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Plastic waste is a global problem that is increasing every year because it is difficult to decompose. This article discusses the growth in waste volume in Indonesia which is triggered by population growth, urbanization, and changes in consumption patterns, as well as the main challenges in waste management at the Bantargebang TPST. Through a qualitative approach and case studies, this article highlights the need for a comprehensive approach to waste management, including the establishment of waste banks and increasing public awareness. The main challenges at the Bantargebang TPST include decreasing capacity and difficulties in handling single-use plastic waste. The proposed solutions include expanding TPST capacity, implementing environmentally friendly technology, increasing public awareness, developing adequate infrastructure, and greater funding allocation. Collaboration between the government, the private sector and the community is the key to overcoming this challenge and building a sustainable and environmentally friendly waste management system at the Bantargebang TPST.